1971
DOI: 10.1021/ja00733a037
|View full text |Cite
|
Sign up to set email alerts
|

Solvolytic reactions of endo-bicyclo[3.2.1]oct-6-en-8-yl tosylate

Abstract: The rates of solvolysis of endo-bicyclo[3.2.1]oct-6-en-8-yl tosylate have been determined in acetic acid and ethanol-water mixtures. Product studies indicated that only products with the parent structure were formed. Both the results of product studies and interpretation of rate data support a significant amount of anchimeric assistance by the carbon-carbon double bond.the known ezzz/o-bicyclo[3.2.1]octan-8-ol.10 The nmr spectrum of 9 had absorptions at 4.13 (m, 2, CH=CH), 5.25 (t, 1, CHOAc), 7.48 (m, 2, bridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1971
1971
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This aliquot was also stored at 4 °C. After removal of solvent, the spectra of the aliquot and the main reaction mixture (230 mg crude; 20-25% material loss during photolysis) both revealed the same new product, trans-2methoxycyclohex-3-ene-l-carboxylic acid (7), formed from opening of the ß-lactone: IR 3500-2500 (s), 1710 (s, br), 1644 (w), 1095 (m, br) cm-1; NMR 1.43-2.83 (m), 3.30 (s, 3 ), 4.0 (m), 5.70 (s with fine structure, 2 H), 9.70 (br s, 1 H; variable).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This aliquot was also stored at 4 °C. After removal of solvent, the spectra of the aliquot and the main reaction mixture (230 mg crude; 20-25% material loss during photolysis) both revealed the same new product, trans-2methoxycyclohex-3-ene-l-carboxylic acid (7), formed from opening of the ß-lactone: IR 3500-2500 (s), 1710 (s, br), 1644 (w), 1095 (m, br) cm-1; NMR 1.43-2.83 (m), 3.30 (s, 3 ), 4.0 (m), 5.70 (s with fine structure, 2 H), 9.70 (br s, 1 H; variable).…”
Section: Methodsmentioning
confidence: 99%
“…A sample of 8 (15 mg) was hydrogenated (100%) using the same conditions as for 10. The product was identified as methyl trans-2methoxycyclohexane-l-carboxylate (9), having IR and NMR spectra identical with an authentic sample4 prepared from methyl transcyclohexan-2-ol-l-carboxylate8 by treatment with diazomethane in the presence of boron trifluoride etherate: IR 2933 (s), 2856 (w), 2824 (w), 1738 (s), 1447 (w), 1428 (w), 1374 (w), 1358 (w), 1322 (w), 1258 (w), 1242 (m), 1188 (m), 1167 (m), 1121 (w), 1096 (m), 1033 (w), 989 (w), 925 (w) cm-1; NMR 0.95-2.45 (m, 9 H), 3.23 and 3.27 (overlapping s, 3 H, and m, 1 H, respectively), 3.60 A sample of methyl c ¡'s -2methoxy cy clohexane -1 -carboxy late was prepared in the same manner and was shown to be different (IR, NMR) from 9. exo-3-Oxatricyclo[3.3.1.02 '4]nonan-9-one (2). Bicyclo[3.2.1[oct-6-en-8-one9,10 (12; 1.0 g, 8.2 mmol crude) in methylene chloride (28 mL) was added to a cold (4 °C) solution of m-chloroperbenzoic acid (1.85 g, 9.0 mmol; 85% pure) in methylene chloride (42 mL) and stirred for 3 h at room temperature under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that halonium ions are much more soluble in S02 than in S02C1F. 34 This may cause the different behavior in ionization of trans-1,2-dibromocyclohexane. A similar ion mixture was obtained when isomeric 1,4-dibromocyclohexanes were ionized in either SbF5-S02 or SbF5-FS03H-S02 solution at -60°, indicating that they both form similar ions.…”
Section: Obsmentioning
confidence: 99%
“…For example, in 1967 Hanack and Riedlinger reported that A2-cyclobutenylmethyl tosylate (15) undergoes hydrolysis to give cyclopent-3-en-l-ol (16) as the major product (eq l). 13 Further, 4-bromocyclopentene (5) unable to contribute to the resolution of the claim that there indeed is a 1,3 orbital interaction in the cyclopent-3-en-1 -yl system.…”
mentioning
confidence: 97%
“…4 These results are in line with the conclusion that the degree of puckering in the cyclopentene ring and hence the distance between the -electron cloud of the double bond and the developing cationic center must be crucial in determining the overall effect of anchimeric assistance. 5 The importance of this steric requirement can be seen by comparing the homologous series of bicyclo[2.1.zi] compounds ( 6) where = 1-3 ( = 0 for cyclopentene). Thus in 1969 Masamune and co-workers6 reported that the ace-tolysis of exo-6-bicyclo[2.1.1 ]hex-2-en-6-yl tosylate ( 8) is 5 X 1016 times faster than that of exo-bicyclo[2.1.1]hex-6-yl tosylate (7) In 1955, Winstein et al noted that zznZz-7-norbornenyl tosylate (2) undergoes acetolysis 10" times faster than 7norbornyl tosylate (l).2 In 1971, Hess5 reported that the acetolysis of ezzz/o-bicyclo[3.2.1 ]oct-6-en-8-yl tosylate (10) was 1.9 X 105 times faster than that of endo-bicyclo[3.2.1]oct-8-yl tosylate (9) Clearly, the relative rates show a definite trend with the increase of the distance between the carbon-carbon double bond and the developing carbonium ion center.…”
mentioning
confidence: 99%